2009
DOI: 10.1017/s0007114509359127
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin reduces systolic blood pressure and plasma oxidised low-density lipoprotein concentrations in overweight subjects with a high-cardiovascular disease risk phenotype: a double-blinded, placebo-controlled cross-over study

Abstract: Regular consumption of flavonoids may reduce the risk for CVD. However, the effects of individual flavonoids, for example, quercetin, remain unclear. The present study was undertaken to examine the effects of quercetin supplementation on blood pressure, lipid metabolism, markers of oxidative stress, inflammation, and body composition in an at-risk population of ninety-three overweight or obese subjects aged 25-65 years with metabolic syndrome traits. Subjects were randomised to receive 150 mg quercetin/d in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
356
2
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 485 publications
(384 citation statements)
references
References 47 publications
17
356
2
9
Order By: Relevance
“…No effect of the HP apple on BP could be observed. Quercetin, one of the phenolic constituents, was shown to reduce BP in hypertensive subjects at a dose of 150 mg/day (Egert et al, 2009). The lack of effects observed here is most likely explained by the much lower intake of quercetin (about 12 mg/day).…”
Section: Polyphenol-rich Apple and Endothelial Function S Auclair Et Almentioning
confidence: 56%
“…No effect of the HP apple on BP could be observed. Quercetin, one of the phenolic constituents, was shown to reduce BP in hypertensive subjects at a dose of 150 mg/day (Egert et al, 2009). The lack of effects observed here is most likely explained by the much lower intake of quercetin (about 12 mg/day).…”
Section: Polyphenol-rich Apple and Endothelial Function S Auclair Et Almentioning
confidence: 56%
“…On one hand, epidemiological studies have concluded that a high flavonoid intake benefits health (23,99) and certain lifespan studies in worms, flies and even mice show that flavonoids could promote longevity. On the other hand, the findings in mammalian model organisms are contradictory and health-related data on flavonoids in human subjects have been obtained from epidemiological Literature review of flavonoids and lifespan in model organisms…”
Section: Resultsmentioning
confidence: 99%
“…A dosage of approximately 130 mg quercetin was chosen, since it has been shown to lower resting systolic blood pressure, pulse pressure and plasma concentrations of oxidised LDL in our previous placebocontrolled cross-over study in overweight patients with a high CVD risk phenotype (9,10) . With both treatments, cereal bars and capsules, quercetin was administered as quercetin aglycone.…”
mentioning
confidence: 99%